Religion contributions nella sfera pubblica: uno sguardo critico alla lettura di Jeremy Waldron (Stato, Chiese e pluralismo confessionale, 2015)
Contributo sottoposto a valutazioneSOMMARIO: 1. Il dibattito sul ruolo delle voci religiose nella sfera pubblica – 2.La peculiare strategia di Jeremy Waldron: theoretical authorities e practical authorities - 3.- Implicazioni metaetiche e operative dell’appello alle theoretical authorities – 4. Il problema dell’inintelligibilità delle argomentazioni religiose – 5. Dall’inintelligibile all’universalizzabile. Le ragioni di un sostanziale fraintendimento. pdf Scarica il testo completo dell'articoloAbstract: Religion Contributions in the public sphere: a critical reading to the position of Jeremy Waldron. The article focuses on the Jeremy Waldron’s lecture of the relationshipbetween religion and democracy. Waldron argues that in public deliberationsreligious citizens can refer directly to religious arguments making reference to the "theoretical authority” of religion. The religious commandments would be worth, in the field of morality, like Paul Krugman’s theories in the field ofeconomy; so when, in the political public square, arguments based on religious beliefs are produced it sounds equivalent to make calling, exclusively, to the"theoretical authority" of religion, not certainly to his authority practice.